SOE Reform : Time for Serious Corporate Governance - Speakman, John (World Bank, Washington, DC, 2017)
This policy paper is motivated by the Government's 'Pakistan: framework for Economic Growth (FEG) 2011' which places weak corporate governance at the top of the 'software' constraints to growth. The efforts to reform the State-Owned Enterprises (SOEs) have stalled in Pakistan for almost five years with significant negative implications not only in terms of fiscal losses, but also deteriorated and cost-ineffective service delivery. The paper suggests a number of urgent policy measures designed to improve the efficiency and effectiveness of SOEs. These include basic governance reforms, revamped commercialization processes and enhanced market regulations. The paper also provides some perspectives on international experience on SOE reforms combined with some suggestions on how the Government can move forward.